Efecto de cinco dosis de bionutriente liquido(strong-phos) en el rendimiento del cultivo de caupi(vigna unguiculata(L.) walp), en el fundo Miraflores - UNSM-T - Guevara Montenegro, Juber (2012)
This research paper entitled "Effect of five doses of liquid bionutrient (Strong-phos) in crop yield of cowpea (Vigna unguiculata (L.) Walp) in fundo Miraflores – UNSM-T". The land is owned by the National University of San Martin - Tarapoto, which is located in the sector Ahuashiyacu, District Band Shilcayo, Province of San Martin. This study was conducted from October 4, 2011 until January 16, 2012. Design we used a randomized complete block with 6 treatments and 3 replications. The planting was done on October 16, 2011 with a spacing of 0,60 m between rows and 0.25 m between coups, the application of liquid bionutrient was performed at the beginning of flowering at 35 days after planting, with straight hand sprinkler crop leaves. The specific variables indicate that the treatment T5 (1 200 ml dose of strong-phos) is the best in performance has responded with 1 028,67 kg.ha-1; and in terms of profitability with net income of S/. 420,41 and a B/C ratio of 0,21; followed by treatment T4 (1 100 ml dose of strong-phos), T3 (1 000 ml dose of strong-phos), T2 (900 ml dose of strong-phos) and T1 (800 ml dose of strong-phos) who obtained yields of 937,93 kg.ha-1; 890,53 kg.ha-1; 819,83 kg.ha-1 and 693,07 kg.ha-1 respectively and net income of S/. 253,03; S/.159,67; S/. 40,39 and S/. -213,44 respectively and a B/C of 0.13, 0.08, 0.02 and -0,11 respectively; and finally the control treatment T6 (without dose strong-phos) with 616,83 kg.ha-1 also expresses net income of S/. -118,01 and a B/C ratio of -0,07; ahead of only T1 (800 ml dose of strong-phos).